Reflection in learning and professional development - Moon, Jennifer (New York: Harvard Education Press, 2005)
Contents: The literature of reflection, some background to the study of reflection, the backbone philosophies of reflection - Dewey and Haberms, reflection in experiential learning, reflection in professional practice - the work of Donald Schon, reflective practice in the professions - a theoretical stance, reflection in learning.
Include appendix
Keywords: Educación - Desarrollo profesional; Professional Development